Resilience of Meat Supply Chains during and after COVID-19 Crisis - Gunta Grinberga-Zalite; Irina Pilvere; Aina Muska; Zenija Kruzmetra (Emerging Science Journal, 2021)
To protect their population during pandemic outbreak, countries apply several preventive restrictions and even shut down their economies to slow the spread of the coronavirus. Since food supply chains in developed countries are complicated and dependent on their external suppliers, these restrictions cause not only economic but also social tension. The limited access to raw materials, packaging material and labour force result in the increasing prices of food products, which forces the population to refuse from quality food products. In the European Union food supply chains, which are negatively affected by protectionist elements and COVID-19 restrictions, the room for manoeuvre of Latvia’s small open economy is limited. The current paper analyses the impact of COVID-19 crisis on global food industry, providing a deeper insight into the case study of Latvia meat supply chains’ experience in overcoming pandemic risks. The research outcomes lead to the conclusion that although COVID-19 impact during first breakout has not caused unexpected and serious consequences for the meat sector companies, the main internal and external risks are associated with further uncertainty and instability in the EU markets. Based on extensive analysis of meat sector specifics, the authors have summarized the recommendations for meat sector companies to better prepare for further potential pandemic situations. Doi: 10.28991/esj-2021-01257 Full Text: PDF